Diversity, population status and communities’ perception towards Osyris lanceolata Hochst & Steudel., in selected Districts of South Omo Zone - Lemage, Belayneh; Tsegaye, Mintesnot; Tesema, Shemelis (Journal of Science and Development, 2021)
Osyris lanceolata is among the sandalwood species known for the production of fragrant-scented wood from which sandalwood essential oil is extracted. The present study was designed to assess the diversity, population status and community’s perception towards O. lanceolata in Hamer and Bena-Tsemay districts, Southern Ethiopia. Multi-stage sampling procedure was employed to conduct this study in purposively selected districts. Data collected through household surveys, local informants’ interviews, direct observation, and systematic random sampling design were used based on the line transect approach for vegetation inventory. About seventy-one (71) respondents were used for the household questionnaire survey to produce basic information, from which 77.5% were male and 22.5% female. Quadrants used for vegetation survey were 27 having 20 m x 20 m plot size. Composition of vegetation data associated with Osyris lanceolata comprised of 46 species, from which 27 and 36 species were in Hamer and Bena-Tsemay disrticts, respectively. The occurrence of Osyris lanceolata showed a decreasing trend in the natural forest due to overexploitation. Based on the findings of the present study the resource around the pastoral and agro-pastoral community needs intensive management to conserve and use important species in sustainable manner. Less consideration to natural resources brings huge ecological, economic and social problems associated with the extinction of extinction of this important species.